A study of the government and media discourse on active ageing in Singapore and its effects on the lived experiences of Singapore seniors - BROOKE, Mark (Advances in Social Sciences Research Journal, 2014)
Similarly to other countries around the world, Singapore is facing the problem of an increasingly ageing population. The number of elderly is expected to triple in the next two decades. One effect of this is the requirement of an elderly workforce to maintain social and economic stability. However, for this to be an effective solution to the demographic dilemma, the elderly must be healthy. Thus, an emphasis on active ageing through engagement in sport participation is encouraged. However, it seems that despite the government’s rhetoric that it is implementing diverse and wide-scale programmes in a bid to help the elderly age successfully, actual participation among seniors in these activities, remains low. One reason for this, emerging from empirical interviews, is that despite knowledge of the ageing population, and the benefits of regular exercise, seniors are not sufficiently aware of the programmes implemented by the government. Based on the data compiled from this study, it is therefore recommended that more be done to maximise the potential of sporting campaigns at community and wellness centres.